A new approach for freshwater production and energy recovery from an oil field. (April 2020) - Memon, Salman; Kim, Young-Deuk; Soomro, Sadam; Soomro, Mujeeb Iqbal; Kim, Woo-Seung
Highlights: A novel RO system with energy recovery was devised to save energy consumption. The three RO configurations were compared with respect to energy consumption. A sensitivity analysis was performed on the effect of parameters on energy recovery. Filtration loss had a greater effect on SEC than friction loss and osmotic pressure. Increasing feed pressure increases electrical energy consumption, but lowers SEC. Abstract: This paper presents a new approach to recover energy and producing freshwater from an oil and gas field using a reverse osmosis (RO) system. We proposed three different RO system configurations: (i) the RO system without energy recovery (i.e., configuration 1), (ii) the RO system with one energy recovery device (i.e., configuration 2), and (iii) the RO system with two energy recovery devices (i.e., configuration 3). Each specific energy consumption (SEC) was then analyzed by solving the mathematical model of RO using MATLAB software. As the feed pressure increased from 4.559 to 6.586 MPa, the SEC decreased from 12.235 to 0.977 kW h/m 3 for configuration 1, from 10.680 to 0.727 kW h/m 3 for configuration 2, and from 3.367 to 0.323 kW h/m 3 for configuration 3, respectively, thus indicating the lowest SEC in configuration 3. In addition, the sensitivity analysis results showed that the SEC decreases significantly with an increase in the stream (crude oil, natural gas, and produced water) pressure, flow rate, and density. In conclusion, the RO system of configuration 3 exhibited a significant decrease in SEC, and freshwater from the RO system makes it beneficial in water scarce regions.